Photo-thermal and photocatalytic composite system and preparation method thereof

By loading copper-titanium oxide and ruthenium on melamine carbide foam support, the photothermal and photocatalytic composite system is formed, which solves the problems of insufficient solar energy utilization and difficulty in catalyst recovery in traditional photocatalytic hydrogen production systems, and achieves efficient solar energy utilization and catalyst utilization reserve.

CN119455819AActive Publication Date: 2025-02-18NINGBO DIGITAL TWIN (EASTERN UNIV OF TECH) RES INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411437107.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Traditional photocatalytic hydrogen production systems have problems such as insufficient solar energy utilization, difficulty in recycling photocatalysts and slow reaction kinetics.

Method used

Using a photothermal and photocatalytic composite system, the system includes a melamine carbide foam with a porous structure as a support, a copper titanium oxide as a photocatalyst and a ruthenium as an auxiliary agent, absorbs solar energy through the photothermal material to generate water vapor, and in the light Photocatalytic hydrogen production is carried out under the action of the catalyst.

Benefits of technology

It achieves higher solar energy utilization, catalyst retention and hydrogen production efficiency, reduces material costs, and improves the environmental adaptability and stability of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455819A_ABST
    Figure CN119455819A_ABST
Patent Text Reader

Abstract

The invention provides a photo-thermal and photocatalysis composite system and a preparation method thereof, and relates to the technical field of photocatalysis. The photo-thermal and photocatalytic composite system comprises a floating carrier with a porous structure and a composite photo-thermal catalyst loaded on the upper half part of the floating carrier; in the photo-thermal and photo-catalytic process, the photo-thermal and photo-catalytic composite system is in a semi-immersed state, the upper half part used for photo-catalytic hydrogen production reaction floats above the liquid level, and the lower half part used for transporting water vapor is immersed below the liquid level. Compared with a traditional photo-thermal system, photo-thermal and photocatalysis are compounded in the same system, so that continuous proceeding of photo-thermal and photocatalysis is achieved, and higher water evaporation rate and hydrogen production efficiency are achieved under the same sun irradiation condition; the composite photo-thermal catalyst is loaded on the floating carrier with the porous structure, so that the continuous leaching of the composite photo-thermal catalyst is effectively reduced, the loss of the composite photo-thermal catalyst is reduced, and the retention rate of the composite photo-thermal catalyst is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and in particular to a photothermal and photocatalytic composite system and a preparation method thereof. Background Art

[0002] Energy is an important material basis for the survival and development of human society. At present, the energy used by humans is mainly non-renewable energy, mainly fossil fuels. It is estimated that fossil fuels, mainly oil, natural gas, and coal, will be exhausted before 2050. At the same time, SO2 generated by the use of fossil fuels 2 , CO 2 Harmful gases such as carbon monoxide and other pollutants have caused a series of environmental problems such as acid rain and greenhouse effect. Energy issues have become a huge obstacle to social development. Therefore, in order to achieve sustainable social development, the development of clean, efficient and renewable new energy is imminent.

[0003] Hydrogen energy is considered an ideal secondary energy source because of its high calorific value, clean products, and abundant reserves of hydrogen on the earth. Photocatalytic technology uses photocatalysts to absorb sunlight, causing the catalyst to excite holes and electrons, where the holes are consumed by sacrificial agents in the reaction system, while the electrons react with water to produce hydrogen. The entire photohydrogen production process is green and pollution-free, and is one of the most ideal ways to obtain hydrogen energy. However, traditional photocatalytic hydrogen production systems have problems such as insufficient solar energy utilization, difficulty in photocatalyst recovery, and slow reaction kinetics. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a photothermal and photocatalytic composite system and a preparation method thereof. The prepared photothermal and photocatalytic composite system has the advantages of high solar energy utilization rate, high catalyst retention rate and high hydrogen production efficiency.

[0005] The present invention provides a photothermal and photocatalytic composite system, comprising a photothermal material, a photocatalyst and an auxiliary agent, wherein the photocatalyst and the auxiliary agent are loaded on the upper half of the photothermal material, the photothermal material is a carbonized melamine foam carrier with a porous structure, the photocatalyst comprises copper titanium oxide, and the auxiliary agent comprises ruthenium. During the photothermal and photocatalytic process, the photothermal and photocatalytic composite system is in a semi-immersed state, the upper half of the photothermal material loaded with the photocatalyst and the auxiliary agent floats above the liquid surface and is used for photocatalytic hydrogen production from water vapor, and the lower half of the photothermal material is immersed below the liquid surface and is used for absorbing solar energy to generate water vapor and transport water vapor.

[0006] Under solar radiation, the photothermal and photocatalytic composite system provided by the present invention quickly generates water vapor through the action of the carbonized melamine foam carrier of the photothermal material and the auxiliary agent ruthenium, and then the water vapor is rapidly diffused to the active site with the help of the porous structure of the carbonized melamine foam carrier, and continuously photocatalytically produces hydrogen under the action of the photocatalyst copper titanium oxide and the auxiliary agent ruthenium; compared with the traditional photothermal and photocatalytic system, the photothermal and photocatalytic composite material provided by the present invention realizes the continuous progress of photothermal and photocatalysis by combining photothermal and photocatalysis in the same material, realizes a higher water evaporation rate and hydrogen production efficiency under the same solar irradiation conditions, and improves the utilization efficiency of solar energy; and the composite material effectively reduces the continuous leaching of the composite photothermal catalyst by loading the composite photothermal catalyst on a floating carrier with a porous structure, reduces the loss of the composite photothermal catalyst during the catalytic process, improves the retention rate of the composite photothermal catalyst, and also improves the continuous operation stability of the composite photothermal catalyst.

[0007] In a possible embodiment, the additive further comprises Mxenes nanosheets, and the material of the Mxenes nanosheets is Ti 3 C 2 . Mxenes nanosheets are used as additives. Since Mxenes nanosheets have a large specific surface area, they can provide more active sites and further improve the efficiency of catalytic hydrogen production.

[0008] In a possible implementation, the carbonized melamine foam carrier is prepared by annealing melamine foam.

[0009] The present invention also provides a method for preparing the above-mentioned photothermal and photocatalytic composite system, comprising the following steps: S1, melamine foam is annealed to obtain a carbonized melamine foam carrier with a porous structure; S2, adding titanium tetrachloride liquid to an aqueous solution containing urea and copper chloride, stirring, heat preservation and annealing to obtain copper titanium oxide (CuTiO x ); S3, the copper titanium oxide described in step S2 is ultrasonically dissolved in a mixture of deionized water and ethanol, a ruthenium chloride solution is added during the ultrasonic dissolution process, and then the Mxenes nanosheet solution is added, and the mixture is evenly mixed to obtain a precursor solution; S4, immersing the upper part of the carbonized melamine foam carrier with a porous structure obtained in step S1 in the precursor solution, and then drying it to obtain the photothermal and photocatalytic composite system.

[0010] In a possible implementation manner, the temperature of the annealing treatment in step S1 is 400-600°C.

[0011] In a possible implementation manner, the annealing treatment time in step S1 is 1-3 h.

[0012] In a possible implementation manner, the concentration of urea in the aqueous solution in step S2 is 40-60 mg / mL.

[0013] In a possible implementation, the concentration of the copper chloride in the aqueous solution in step S2 is 27-110 mg / mL.

[0014] In a possible implementation manner, in step S2, the volume ratio of the titanium tetrachloride liquid to the aqueous solution is 1:(50-70).

[0015] In a possible implementation manner, the stirring time in step S2 is 30-60 min.

[0016] In a possible implementation manner, the insulation temperature in step S2 is 80-110° C. and the insulation time is 12-24 h.

[0017] In a possible implementation manner, the annealing in step S2 has a heating rate of 2-5°C / min, a temperature of 300-500°C, and a time of 1-3 h.

[0018] In a possible implementation manner, the volume ratio of the ethanol to the deionized water in the mixed solution in step S3 is 2:1.

[0019] In a possible implementation manner, the ultrasonic dissolution time in step S3 is 10-60 min.

[0020] In a possible implementation, the concentration of the ruthenium trichloride solution in step S3 is 5 mg / mL.

[0021] In a possible implementation, the solvent of the ruthenium trichloride solution in step S3 is deionized water.

[0022] In a possible embodiment, the concentration of the Mxenes nanosheet solution in step S3 is 1-5 mg / mL, preferably 3 mg / mL.

[0023] In a possible embodiment, the method for preparing the Mxenes nanosheet solution in step S3 comprises the following steps: 3 AlC 2 The reaction is carried out in an aqueous solution containing LiF and HCl, and the solution after the reaction is washed by centrifugation to obtain a precipitate. The precipitate is prepared into an aqueous solution and subjected to ultrasonic peeling under ice bath conditions, and then the upper layer solution is centrifuged to obtain a MXenes nanosheet solution. Generally, the MXene contained in the upper layer solution is a few layers or a single layer.

[0024] Furthermore, the concentration of LiF in the aqueous solution is 80 mg / mL.

[0025] Furthermore, the concentration of HCl in the aqueous solution is 9 mol / L.

[0026] Furthermore, the reaction temperature is 20-40°C and the reaction time is 24-36 h.

[0027] Furthermore, the centrifugal washing process is to place the reacted solution in a centrifuge tube, then add water to the centrifuge tube, perform centrifugal washing, pour out the supernatant, repeat the above centrifugal washing steps until the pH value of the solution is 6-7, and obtain the precipitate.

[0028] Furthermore, the temperature of the ice bath is 2-10°C, preferably 4°C.

[0029] Furthermore, the ultrasonic peeling time is 10-15 min.

[0030] Furthermore, the rotation speed of the centrifugal treatment is 2000-3500 rpm and the time is 1-3 h.

[0031] In a possible implementation, in step S4, the carbonized melamine foam carrier is immersed in the precursor solution for the first time and then dried for the first time, and then immersed in the precursor solution for the second time and then dried for the second time to obtain the photothermal and photocatalytic composite system.

[0032] Furthermore, the initial soaking time is 10-30 min.

[0033] Furthermore, the temperature of the first drying and the second drying is 60-110°C.

[0034] Furthermore, the first drying time is 1-3 h.

[0035] Furthermore, the second drying time is 3-6 h.

[0036] The reagents and raw materials used in the present invention are commercially available.

[0037] The positive and progressive effects of the present invention are: The photothermal and photocatalytic composite system provided by the present invention achieves higher solar energy utilization, catalyst retention rate and hydrogen production efficiency under the same solar irradiation conditions compared with traditional photothermal systems; it can also maintain good reaction activity in river water and sea water, showing excellent environmental adaptability, and is suitable for various scenarios such as household water supply, wastewater treatment and seawater desalination; and the use of composite photothermal catalysts that do not require precious metals significantly reduces material costs, while the system's floating design reduces the complexity of installation and maintenance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a physical picture of the melamine foam without annealing treatment in Example 1.

[0039] Figure 2 This is a physical picture of the carbonized melamine foam obtained by annealing treatment in Example 1.

[0040] Figure 3 This is a SEM image of the carbonized melamine foam obtained by annealing in Example 1.

[0041] Figure 4 This is the SEM image of the carbonized melamine foam loaded with copper titanium oxide / Mxenes / Ru prepared in Example 1.

[0042] Figure 5 TEM image and element distribution diagram of the copper titanium oxide prepared in Example 1.

[0043] Figure 6 This is a local SEM image of copper titanium oxide / Mxenes / Ru supported on carbonized melamine foam in Example 1.

[0044] Figure 7 TEM image of the Mxenes ultrathin nanosheets prepared in Example 1.

[0045] Figure 8 The UV-VIS spectra of the photothermal and photocatalytic composite systems prepared in Example 1 and Example 2 are shown.

[0046] Fig. 9 This is a data graph of the hydrogen production efficiency of the photothermal and photocatalytic composite system prepared in Example 1 and Example 2. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0048] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0049] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0050] Example 1

[0051] This embodiment provides a photothermal and photocatalytic composite system, which is prepared by the following preparation method: (1) Preparation of floating carriers: The purchased commercial melamine foam was cut into small cubes of 6 cm*3 cm*2 cm, and annealed in a tube furnace. Under the protection of high-purity argon, the heating rate was set to 5 °C / min, the maximum temperature was 400 °C, and the carbonized melamine foam was obtained after natural cooling after keeping the temperature for 1 h. (2) Preparation of copper titanium oxide: D1. Add 50 mL of deionized water into the reactor, add 3 g of urea and 1.9-5.4 g of copper chloride successively under magnetic stirring, and stir until the solution has a uniform color. The stirring time is about 10 min. D2. Slowly drop 1.2 mL of titanium tetrachloride liquid into the solution in step D1, stir vigorously for 30 min, then place in an oven at 90 °C for 12 h, centrifuge 2-3 times, and then dry at 60 °C to obtain dry powder; D3, placing the dried powder in step D2 in a tube furnace, annealing under the protection of high-purity argon, setting the heating rate of the tube furnace to 5 ° C / min, the maximum temperature to 400 ° C, keeping the temperature for 1 h and then cooling naturally to obtain copper titanium oxide (CuTiO x ); (3) Preparation of Mxenes ultrathin nanosheet solution: F1 and 1.6 g LiF were added into 20 mL 9 M HCl solution and stirred for 30 min at 40 °C to form a mixed solution. F2, under stirring conditions, 1g Ti 3 AlC 2 The MAX phase is added to the mixed solution in step F1 in small amounts for several times, with the amount being as small as possible each time, and the adding process is controlled to be more than 30 minutes to obtain a reaction solution; F3, sealing the reaction solution in step F2 in a reaction tank, and stirring the reaction at 40°C for 24 h; F4. After the reaction is completed, the obtained solution is divided into at least 4 equal parts and loaded into 50 mL centrifuge tubes, and then deionized water is added to 45-50 mL for centrifugal washing, and the supernatant is poured out. The above washing steps are repeated several times until the pH value of the solution is 6-7; F5. After washing, the precipitate was redispersed in 20-30 mL of deionized water, shaken thoroughly to mix evenly, and then ultrasonically stripped for 10-15 min in an ice bath at 4°C. F6. After the ultrasonic stripping is completed, centrifuge again for 1 h at a centrifugal speed of 2000-3500 rmp, and then take the upper solution. Generally, the upper solution contains 1-10 layers of MXene nanosheets, i.e., MXene ultra-thin nanosheets. The concentration of MXenes ultra-thin nanosheets in the upper solution is 3 mg / ml. (4) Composite photothermal catalyst CTRM (CuTiO x -Ru-Mxenes ultrathin nanosheets) loading: H1. Prepare copper titanium oxide (CuTiO x ) was placed in a mixture of 5 mL of deionized water and 10 mL of ethanol and ultrasonicated for 30 min, during which 200 ul of a 5 mg / mL ruthenium chloride solution was added every 10 min, and then 400 ul of a 3 mg / mL Mxenes nanosheet solution was added after 10 min to form a solution containing a precursor of a composite photothermal catalyst; H2. Place the carbonized melamine foam obtained in step (1) in the solution containing the precursor of the composite photothermal catalyst in step H1 and soak for 10 min. The soaking area of ​​the carbonized melamine foam is half of the total height of the carbonized melamine foam. Then place it in an oven and keep it at 90°C for 1 h. Then take it out and soak it in the solution containing the precursor of the composite photothermal catalyst again until the solution is completely absorbed. Then place it in the oven again and keep it at 90°C for 3 h.

[0052] Example 2

[0053] This embodiment provides a photothermal and photocatalytic composite system, which is prepared by the following preparation method: (1) Preparation of floating carriers: The purchased commercial melamine foam was cut into small cubes of 6 cm*3 cm*2 cm, and annealed in a tube furnace. Under the protection of high-purity argon, the heating rate was set to 5 °C / min, the maximum temperature was 400 °C, and the carbonized melamine foam was obtained after natural cooling after keeping the temperature for 1 h. (2) Preparation of copper titanium oxide: D1. Add 70 mL of deionized water into the reactor, add 3 g of urea and 1.9-5.4 g of copper chloride successively under magnetic stirring, and stir until the solution has a uniform color. The stirring time is about 10 min. D2. Slowly drop 1.2 mL of titanium tetrachloride liquid into the solution in step D1, stir vigorously for 30 min, then place in an oven at 90 °C for 12 h, centrifuge 2-3 times, and then dry at 60 °C to obtain dry powder; D3, placing the dried powder in step D2 in a tube furnace, annealing under the protection of high-purity argon, setting the heating rate of the tube furnace to 5 ° C / min, the maximum temperature to 400 ° C, keeping the temperature for 1 h and then cooling naturally to obtain copper titanium oxide (CuTiO x ); (3) Composite photothermal catalyst CTR (CuTiO x -Ru) Load: H1. Prepare copper titanium oxide (CuTiO x ) was placed in a mixture of 5 mL of deionized water and 10 mL of ethanol and ultrasonicated for 30 min, during which 400 ul of a 5 mg / mL ruthenium chloride solution was added at intervals of 10 min to form a solution containing a precursor of a composite photothermal catalyst; H2. Place the carbonized melamine foam obtained in step (1) in the solution containing the precursor of the composite photothermal catalyst in step H1 and soak for 10 min. The soaking area of ​​the carbonized melamine foam is half of the total height of the carbonized melamine foam. Then place it in an oven and keep it at 90°C for 1 h. Then take it out and soak it in the solution containing the precursor of the composite photothermal catalyst again until the solution is completely absorbed. Then place it in the oven again and keep it at 90°C for 3 h.

[0054] Example 3

[0055] This embodiment provides a photothermal and photocatalytic composite system, which is prepared by the following preparation method: (1) Preparation of floating carriers: The purchased commercial melamine foam was cut into small cubes of 6 cm*3 cm*2 cm, and annealed in a tube furnace. Under the protection of high-purity argon, the heating rate was set to 5 °C / min, the maximum temperature was 600 °C, and the carbonized melamine foam was obtained after natural cooling after keeping the temperature for 1 h. (2) Preparation of copper titanium oxide: D1. Add 50 mL of deionized water into the reactor, add 3 g of urea and 1.9-5.4 g of copper chloride successively under magnetic stirring, and stir until the solution has a uniform color. The stirring time is about 10 min. D2. Slowly drop 1.2 mL of titanium tetrachloride liquid into the solution in step D1, stir vigorously for 60 min, then place in an oven at 80 °C for 24 h, centrifuge 2-3 times, and then dry at 60 °C to obtain dry powder; D3, placing the dried powder in step D2 in a tube furnace, annealing under the protection of high-purity argon, setting the heating rate of the tube furnace to 2 ° C / min, the maximum temperature to 300 ° C, keeping the temperature for 3 hours and then cooling naturally to obtain copper titanium oxide (CuTiO x ); (3) Preparation of Mxenes ultrathin nanosheet solution: F1 and 1.6 g LiF were added into 20 mL 9 mol / L HCl solution, stirred at 40 °C for 30 min to form a mixed solution. F2, under stirring conditions, 1 g Ti 3 AlC 2 The MAX phase is added to the mixed solution in step F1 in small amounts for several times, with the amount being as small as possible each time, and the adding process is controlled to be more than 30 minutes to obtain a reaction solution; F3, sealing the reaction solution in step F2 in a reaction tank, and stirring the reaction at 20°C for 36 hours; F4. After the reaction is completed, the obtained solution is divided into at least 4 equal parts and loaded into 50 mL centrifuge tubes, and then deionized water is added to 45-50 mL for centrifugal washing, and the supernatant is poured out. The above washing steps are repeated several times until the pH value of the solution is 6-7; F5. After washing, the precipitate was redispersed in 20-30 mL of deionized water, shaken thoroughly to mix evenly, and then subjected to continuous ultrasonic stripping in an ice bath at 10 °C for 10 min. F6. After the ultrasonic stripping is completed, centrifuge again for 1 h at a centrifugal speed of 3500 rmp, and then take the upper solution. Generally, the upper solution contains 1-10 layers of MXene nanosheets, i.e., MXene ultra-thin nanosheets. The concentration of MXenes ultra-thin nanosheets in the upper solution is 3 mg / ml. (4) Composite photothermal catalyst CTRM (CuTiO x -Ru-Mxenes ultrathin nanosheets) loading: H1. Prepare copper titanium oxide (CuTiO x ) was placed in a mixture of 5 mL of deionized water and 10 mL of ethanol and ultrasonically dissolved for 10 min, during which 600 ul of a 5 mg / mL ruthenium chloride solution was added at intervals of 10 min, and then 200 ul of a 5 mg / mL Mxenes nanosheet solution was added after 10 min to form a solution containing a precursor of a composite photothermal catalyst; H2. The carbonized melamine foam obtained in step (1) is placed in the solution containing the precursor of the composite photothermal catalyst in step H1 and soaked for 10 min. The soaked area of ​​the carbonized melamine foam is half of the total height of the carbonized melamine foam. The foam is then placed in an oven and kept warm at 60°C for 3 h. The foam is then taken out and soaked in the solution containing the precursor of the composite photothermal catalyst again until the solution is completely absorbed. The foam is then placed in an oven again and kept warm at 90°C for 6 h.

[0056] Example 4

[0057] This embodiment provides a photothermal and photocatalytic composite system, which is prepared by the following preparation method: (1) Preparation of floating carriers: The purchased commercial melamine foam was cut into small cubes of 6 cm*3 cm*2 cm, and annealed in a tube furnace. Under the protection of high-purity argon, the heating rate was set to 5 °C / min, the maximum temperature was 400 °C, and the carbonized melamine foam was obtained after natural cooling after keeping the temperature for 3 h. (2) Preparation of copper titanium oxide: D1. Add 70 mL of deionized water into the reactor, add 3 g of urea and 1.9-5.4 g of copper chloride successively under magnetic stirring, and stir until the solution has a uniform color. The stirring time is about 10 min. D2. Slowly drop 1.2 mL of titanium tetrachloride liquid into the solution in step D1, stir vigorously for 60 min, then place in an oven at 110 °C for 18 h, centrifuge 2-3 times, and then dry at 60 °C to obtain dry powder; D3, placing the dried powder in step D2 in a tube furnace, annealing under the protection of high-purity argon, setting the heating rate of the tube furnace to 5 ° C / min, the maximum temperature to 500 ° C, keeping the temperature for 1 hour and then cooling naturally to obtain copper titanium oxide (CuTiO x ); (3) Preparation of Mxenes ultrathin nanosheet solution: F1 and 1.6 g LiF were added into 20 mL 9 M HCl solution and stirred at 40 °C for 30 min to form a mixed solution. F2, under stirring conditions, 1 g Ti 3 AlC 2 The MAX phase is added to the mixed solution in step F1 in small amounts for several times, with the amount being as small as possible each time, and the adding process is controlled to be more than 30 minutes to obtain a reaction solution; F3, sealing the reaction solution in step F2 in a reaction tank, and stirring the reaction at 30°C for 30 h; F4. After the reaction is completed, the obtained solution is divided into at least 4 equal parts and loaded into 50 mL centrifuge tubes, and then deionized water is added to 45-50 mL for centrifugal washing, and the supernatant is poured out. The above washing steps are repeated several times until the pH value of the solution is 6-7; F5. After washing, the precipitate was redispersed in 20-30 mL of deionized water, shaken thoroughly to mix evenly, and then ultrasonically stripped for 15 min in an ice bath at 2°C. F6. After the ultrasonic stripping is completed, centrifuge again for 3 h at a centrifugal speed of 2000, and then take the upper solution. Generally, the upper solution contains 1-10 layers of MXene nanosheets, i.e., MXene ultra-thin nanosheets. The concentration of MXenes ultra-thin nanosheets in the upper solution is 3 mg / ml. (4) Composite photothermal catalyst CTRM (CuTiO x -Ru-Mxenes ultrathin nanosheets) loading: H1. Prepare copper titanium oxide (CuTiO x ) was placed in a mixture of 5 mL of deionized water and 10 mL of ethanol and ultrasonically dissolved for 60 min, during which 800 ul of a 5 mg / mL ruthenium chloride solution was added at intervals of 10 min, and then 100 ul of a 1 mg / mL Mxenes nanosheet solution was added after 10 min to form a solution containing a precursor of a composite photothermal catalyst; H2. Place the carbonized melamine foam obtained in step (1) in the solution containing the precursor of the composite photothermal catalyst in step H1 and soak for 30 min. The soaking area of ​​the carbonized melamine foam is half of the total height of the carbonized melamine foam. Then place it in an oven and keep it at 110°C for 1 h. Then take it out and soak it again in the solution containing the precursor of the composite photothermal catalyst until the solution is completely absorbed. Then place it in the oven again and keep it at 90°C for 3 h.

[0058] Effect test results Figure 1 This is a physical picture of the melamine foam without annealing treatment in Example 1. As can be seen from the figure, the untreated melamine foam is white.

[0059] Figure 2 This is a physical picture of the carbonized melamine foam obtained by annealing in Example 1. As can be seen from the figure, after annealing, the melamine foam has been carbonized to form carbonized melamine, which is black.

[0060] Figure 3 This is a SEM image of the carbonized melamine foam obtained by annealing in Example 1. As can be seen from the image, the carbonized melamine foam has a three-dimensional network structure and has a very high porosity.

[0061] Figure 4 This is a SEM image of the carbonized melamine foam loaded with copper titanium oxide / Mxenes / Ru prepared in Example 1. As can be seen from the figure, due to the loading of copper titanium oxide / Mxenes / Ru, part of the grids of the three-dimensional network structure of the carbonized melamine foam are covered by copper titanium oxide / Mxenes / Ru, which can increase the contact area with water vapor and increase the number of active sites.

[0062] Figure 5 TEM image and element distribution diagram of the copper titanium oxide prepared in Example 1. As can be seen from the figure, the synthesized copper titanium oxide contains three elements of copper, titanium and oxygen, and copper, titanium and oxygen are evenly distributed.

[0063] Figure 6 This is a local SEM image of the copper titanium oxide / Mxenes / Ru supported on the carbonized melamine foam in Example 1. As can be seen from the figure, the granular copper titanium oxide / Mxenes / Ru is very evenly distributed.

[0064] Figure 7 This is a TEM image of the Mxenes ultrathin nanosheet prepared in Example 1. As can be seen from the figure, the size of the Mxenes ultrathin nanosheet is about several hundred nanometers, and the contrast between the Mxenes ultrathin nanosheet and the background in the figure is very small, indicating that the thickness of the Mxenes ultrathin nanosheet is relatively thin.

[0065] Figure 8 The UV-VIS spectra of the photothermal and photocatalytic composite systems prepared in Example 1 and Example 2. Among them, MS represents melamine foam without annealing treatment, AMS represents carbonized melamine foam after annealing treatment, AMS / Mxenes represents carbonized melamine foam loaded with Mxenes ultrathin nanosheets, AMS / CT / R represents a carbonized melamine foam system loaded with copper titanium oxide and ruthenium, and AMS / Mxenes / CT / R represents a carbonized melamine foam system loaded with copper titanium oxide, Mxenes ultrathin nanosheets and ruthenium. It can be seen from the data in the figure that the light absorption performance of carbonized melamine foam after annealing is significantly better than that of melamine foam without annealing. For AMS / Mxenes, AMS / Mxenes / CT / R and AMS / Mxenes / CT / R, the light absorption performance is slightly reduced due to the blocking effect of copper titanium oxide, Mxenes ultra-thin nanosheets and ruthenium, but the reduction is small.

[0066] Fig. 9 The figure is a hydrogen production efficiency data diagram of the photothermal and photocatalytic composite system prepared in Example 1 and Example 2. The pink mark (Floating-AMS) in the figure represents the hydrogen production efficiency data of the photothermal and photocatalytic composite system loaded on the carbonized melamine foam, and the blue standard (particles) represents the hydrogen production efficiency data of the system without loading and using only granular catalysts. x (Ru20%) indicates a system where copper titanium oxide is a photocatalyst and ruthenium is an auxiliary agent. x (Ru20%Mxenes5%) represents a system with copper titanium oxide as a photocatalyst and ruthenium and Mxenes ultra-thin nanosheets as additives. From the data in the figure, it can be seen that the hydrogen production efficiency of the system loaded on carbonized melamine foam is significantly higher than that of the system without loading, and the hydrogen production efficiency of the system using ruthenium and Mxenes ultra-thin nanosheets as additives is better than that of the system using only ruthenium as an additive. Figure 8 and Fig. 9 It can be seen from the data in that the photothermal and photocatalytic composite system provided by the present invention has the advantages of high solar energy utilization and high hydrogen production efficiency.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A photothermal and photocatalytic composite system, characterized in that: The invention comprises a photothermal material, a photocatalyst and an auxiliary agent, wherein the photocatalyst and the auxiliary agent are loaded on the upper part of the photothermal material, the photothermal material is a carbonized melamine foam carrier with a porous structure, the photocatalyst comprises copper titanium oxide, and the auxiliary agent comprises ruthenium. During the photothermal and photocatalytic process, the photothermal and photocatalytic composite system is in a semi-immersed state, the upper part of the photothermal material loaded with the photocatalyst and the auxiliary agent floats above the liquid surface and is used for photocatalytic hydrogen production from water vapor, and the lower part of the photothermal material is immersed below the liquid surface and is used for absorbing solar energy to generate water vapor and transport water vapor.

2. The photothermal and photocatalytic composite system according to claim 1, characterized in that: The auxiliary agent also includes Mxenes nanosheets, and the material of the Mxenes nanosheets is Ti3C2: And / or, the carbonized melamine foam carrier is prepared by annealing melamine foam.

3. A method for preparing the photothermal and photocatalytic composite system according to claim 1 or 2, characterized in that: The following steps are involved: S1, melamine foam is annealed to obtain a carbonized melamine foam carrier with a porous structure; S2, adding titanium tetrachloride liquid to an aqueous solution containing urea and copper chloride, stirring, keeping warm and annealing to obtain copper titanium oxide; S3, the copper titanium oxide described in step S2 is ultrasonically dissolved in a mixture of deionized water and ethanol, a ruthenium chloride solution is added during the ultrasonic dissolution process, and then the Mxenes nanosheet solution is added, and the mixture is evenly mixed to obtain a precursor solution; S4, immersing the upper part of the carbonized melamine foam carrier with a porous structure obtained in step S1 in the precursor solution, and then drying it to obtain the photothermal and photocatalytic composite system.

4. The method for preparing the photothermal and photocatalytic composite system according to claim 3, characterized in that: The temperature of the annealing treatment in step S1 is 400-600°C; And / or, the annealing treatment time in step S1 is 1-3 h.

5. The method for preparing the photothermal and photocatalytic composite system according to claim 3, characterized in that: The concentration of urea in the aqueous solution in step S2 is 40-60 mg / mL; And / or, the concentration of the copper chloride in the aqueous solution in step S2 is 27-110 mg / mL; And / or, the volume ratio of the titanium tetrachloride liquid to the aqueous solution in step S2 is 1:(50-70); And / or, the stirring time in step S2 is 30-60 min; And / or, the insulation temperature in step S2 is 80-110° C. and the time is 12-24 h; And / or, the annealing in step S2 has a heating rate of 2-5°C / min, a temperature of 300-500°C, and a time of 1-3 h.

6. The method for preparing the photothermal and photocatalytic composite system according to claim 3, characterized in that: The volume ratio of the ethanol to the deionized water in the mixed solution of step S3 is 2:1; And / or, the ultrasonic dissolution time in step S3 is 10-60 min; And / or, the concentration of the ruthenium chloride solution in step S3 is 5 mg / mL; And / or, the solvent of the ruthenium trichloride solution in step S3 is deionized water; And / or, the concentration of the Mxenes nanosheet solution in step S3 is 1-5 mg / mL; And / or, the preparation method of the Mxenes nanosheet solution in step S3 comprises the following steps: MAX phase Ti3AlC2 reacts in an aqueous solution containing LiF and HCl, the solution after the reaction is centrifuged and washed to obtain a precipitate, the precipitate is configured into an aqueous solution and ultrasonically stripped under ice bath conditions, and then the upper layer solution is taken and centrifuged to obtain a Mxenes nanosheet solution.

7. The method for preparing a photothermal and photocatalytic composite system according to claim 6, characterized in that: The concentration of LiF in the aqueous solution is 80 mg / mL; and / or, the concentration of HCl in the aqueous solution is 9 mol / L; And / or, the reaction temperature is 20-40°C and the reaction time is 24-36 h; And / or, the centrifugal washing process is to place the solution after the reaction in a centrifuge tube, then add water to the centrifuge tube, perform centrifugal washing, pour out the supernatant, repeat the above centrifugal washing steps until the pH value of the solution is 6-7, and obtain the precipitate; And / or, the temperature of the ice bath is 2-10°C; And / or, the ultrasonic stripping time is 10-15 min; And / or, the rotation speed of the centrifugal treatment is 2000-3500 rpm and the time is 1-3 h.

8. The method for preparing the photothermal and photocatalytic composite system according to claim 7, characterized in that: The concentration of the Mxenes nanosheet solution in step S3 is 3 mg / mL; And / or, the temperature of the ice bath is 4°C.

9. The method for preparing a photothermal and photocatalytic composite system according to claim 3, characterized in that: In step S4, the carbonized melamine foam carrier is immersed in the precursor solution for the first time and then dried for the first time, and then immersed in the precursor solution for the second time and then dried for the second time to obtain the photothermal and photocatalytic composite system.

10. The method for preparing the photothermal and photocatalytic composite system according to claim 9, characterized in that: The initial soaking time is 10-30 min; And / or, the temperature of the first drying and the second drying is 60-110°C; And / or, the first drying time is 1-3 h; And / or, the second drying time is 3-6 h.

Citation Information

Patent Citations

  • Solar water evaporation purification and decomposition device

    CN107879405A

  • Preparation method and application of novel composite photocatalyst for catalyzing water photolysis to produce hydrogen

    CN111229326A

  • Oxygen vacancy promoted direct Z mechanism mesoporous Cu2O / TiO2 photocatalyst and preparation method thereof

    CN112958061A

  • Super-hydrophobic sponge with photothermal effect and preparation method thereof

    CN113462014A

  • MXene loaded copper-based catalyst as well as preparation method and application thereof

    CN116060069A